Poczucie podmiotowości komunikacyjnej w perspektywie badań nad kompetencjami medialnymi - Szostok-Nowacka, Patrycja (Polityka i Społeczeństwo, 2020)
The aim of the article is to present the concept of the sense of communication subjectivity from the perspective of its usefulness in research on media competences. The author discusses theoretical aspects of human subjectivity connected with communication activity referring to the literature in the field of political science, sociology, and psychology. She constructs a model of the sense of communication subjectivity based on available theories, then she verifies it in the questionnaire research on the relationship between the sense of communication subjectivity and social activity in territorial self-governments of the Śląskie Voivodeship. The results of the survey confirm the research hypothesis, according to which social activity is associated with a sense of communication subjectivity. Apart from the conclusions provided by the survey, the author formulates the proposal of further use of the concept in research on communication in various social situations, especially those involving asymmetric communication, for example, in work environment, health care, education, etc.